Colquhounia root tablet improves diabetic kidney disease by regulating epithelial-mesenchymal transition via the PTEN/PI3K/AKT pathway - Ma, Donghong; Zhang, Jiao; Du, Lu; Shi, Jingjing; Liu, Zhaoyan; Qin, Jilin; Chen, Xiaoxiao; Guo, Minghao (Frontiers in Pharmacology, 2024)
Background: Diabetic kidney disease (DKD) is a severe microvascular complication of diabetes mellitus that can lead to end-stage renal disease. Colquhounia root tablet (CRT) has shown therapeutic potential in treating DKD, but its efficacy and underlying mechanisms remain to be elucidated. Methods: A randomized controlled clinical trial was conducted on 61 DKD patients. The treatment group received CRT in addition to standard therapy, while the control group received standard therapy alone. Treatment efficacy and adverse events were evaluated after 3 months. Additionally, in vitro experiments using human renal tubular epithelial cells (HK-2) were performed to investigate the effect of CRT on high glucose (HG)-induced epithelial-mesenchymal transition (EMT) and the involvement of the PTEN/PI3K/AKT signaling pathway. Results: CRT treatment significantly improved proteinuria and increased the effective treatment rate in DKD patients compared to the control group, with no significant difference in adverse events. Moreover, CRT reversed HG-induced EMT in HK-2 cells, as evidenced by the downregulation of α-SMA and upregulation of E-cadherin at both mRNA and protein levels. Mechanistically, CRT increased PTEN expression and inhibited the PI3K/AKT pathway, similar to the effects of the PI3K inhibitor LY29400. The combination of CRT and LY29400 further enhanced PTEN mRNA expression under HG conditions. Conclusion: CRT effectively improves proteinuria in DKD patients and ameliorates HG-induced EMT in HK-2 cells. The underlying mechanism may involve the upregulation of PTEN and subsequent inhibition of the PI3K/AKT signaling pathway. These findings provide new insights into the therapeutic potential of CRT for DKD treatment.